An evaluation study for teachers of Islamic education In light of the quality of their educational performance in middle school (Journal of the College of Basic Education, 2022)
The current research aims to evaluate teachers of Islamic education in the light of the quality of their educational performance in the preparatory stage. To achieve the objectives of the study, the researchers used the descriptive approach. Islamic education and its teachers in the schools of the General Directorate of Education Rusafa II. The number of members of the main sample in the current research was (50) teachers and (50) schools. The researchers used the Likert scale, the Pearson correlation coefficient, the weighted mean, and the weight percentile to analyze the data and reach the results. The study reached several results, the most important of which are:1- The performance of Islamic education teachers who teach in Baghdad governorate schools was relatively weak.